Numerical Validation of Multiphysic Imperfect Interfaces Models - Dumont, Serge; Serpilli, Michele; Rizzoni, Raffaella; Lebon, Frédéric C. (Frontiers in Materials, 2020)
We investigate some mathematical and numerical methods based on asymptotic expansions for the modeling of bonding interfaces in the presence of linear coupled multiphysics phenomena. After reviewing new recently proposed imperfect contact conditions Serpilli et al. (2019), we present some numerical examples designed to show the efficiency of the proposed methodology. The examples are framed within two different multiphysics theories, piezoelectricity and thermo- mechanical coupling. The numerical investigations are based on a finite element approach generalizing to multiphysics problems the procedure developed in Dumont et al. (2018a)